Exogenous oil supply shocks in OPEC and non-OPEC countries - Jochen Güntner; Johannes Henßler (Johannes Kepler University of Linz, Department of Economics, 2020)
This note expands Kilian's (2008) original time series of exogenous oil supply shocks along two dimensions. First, we extend the sample period and include production shortfalls in OPEC member states during 2004:10-2018:12. Second, we also consider production shortfalls in non-OPEC countries. Our extended series of exogenous oil supply shocks displays statistically significant correlation with alternative estimates of oil supply shocks based on vector-autoregressive models. At the same time, it requires a limited number of assumptions about the counterfactual evolution of production in the countries under consideration rather than the hotly debated identifying restrictions inherent in multivariate structural models.
Keywords: N50; Q31; Q35; 330; Counterfactual analysis; Crude oil production; Exogenous events; Oil supply shocks